From Mindset to Behavior: Analyzing the Determinants Entrepreneurial Intention of Students - Kiagus Azhar Ansori; Ika Febrilia; Sri Novalia; Rizal Syarief (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2025)
Entrepreneurship plays a strategic role in fostering economic independence among the younger generation, yet many students have not realized their entrepreneurial intentions. This study aims to analyze the influence of internal factors (entrepreneurial mindset and fear of failure) and external factors (entrepreneurial knowledge and institutional support) on the entrepreneurial intention of students at the Faculty of Economics and Business, Universitas Negeri Jakarta (FEB UNJ). Using a quantitative explanatory approach, this study involved 138 respondents who had taken an entrepreneurship course. The research instrument was developed based on prior literature and analyzed using multiple linear regression through SPSS. The results indicate that entrepreneurial mindset, entrepreneurial knowledge, and institutional support have a significant positive effect on entrepreneurial intention, while fear of failure has a significant negative effect. The regression model explains 36.7% of the variability in students’ entrepreneurial intention. These findings reinforce the Theory of Planned Behavior, emphasizing the critical role of mindset, knowledge, and supportive environments in shaping students’ entrepreneurial intentions in higher education.